2015
DOI: 10.1007/s10592-015-0737-x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure at the northern range limit of the threatened eastern hog-nosed snake (Heterodon platirhinos)

Abstract: Habitat loss and fragmentation have important consequences for population persistence by reducing dispersal, connectivity, and population size. Characterizing patterns of population genetic structure and gene flow, and testing for the genetic signature of population declines and inbreeding can provide key insights into conservation for at-risk species. We use 12 microsatellite DNA markers to quantify the spatial structuring across two regional populations of the threatened eastern hog-nosed snake (Heterodon pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…However, the level of connectivity to larger contiguous populations in the USA is unknown and requires further research. Similar to the situation with other northern snake populations (e.g., [ 14 , 15 ]), our findings suggest that population subdivision on a regional scale is an important consideration for conservation planning.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, the level of connectivity to larger contiguous populations in the USA is unknown and requires further research. Similar to the situation with other northern snake populations (e.g., [ 14 , 15 ]), our findings suggest that population subdivision on a regional scale is an important consideration for conservation planning.…”
Section: Discussionsupporting
confidence: 85%
“…It is important to know whether this species needs to be managed as a single entity or multiple designatable units (DUs). Other recent studies have revealed critical mismatches between the number and extent of snake populations based on genetic markers, and the scale of conservation plans or management units (e.g., [ 15 , 52 ]). According to guidelines from the Committee on the Status of Endangered Wildlife in Canada (COSEWIC), the advisory body to the federal Minister of the Environment, populations warrant separate DU status if they are both ‘discrete’ and ‘significant’ [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation